2003
DOI: 10.1073/pnas.2433882100
|View full text |Cite
|
Sign up to set email alerts
|

Hypervirulent mutant ofMycobacterium tuberculosisresulting from disruption of themce1operon

Abstract: An estimated one-third of the world's population is latently infected with Mycobacterium tuberculosis, the etiologic agent of tuberculosis. Here, we demonstrate that, unlike wild-type M. tuberculosis, a strain of M. tuberculosis disrupted in the mce1 operon was unable to enter a stable persistent state of infection in mouse lungs. Instead, the mutant continued to replicate and killed the mice more rapidly than did the wild-type strain. Histological examination of mouse lungs infected with the mutant strain rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
216
3
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(238 citation statements)
references
References 22 publications
(28 reference statements)
17
216
3
1
Order By: Relevance
“…Previous studies have implicated the mce operon (53) and several two-component signaling modules (54) as additional negative regulators of M. tuberculosis virulence. In these studies, however, the pleiotropic nature of the mutants may complicate efforts to define the molecular underpinnings of the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated the mce operon (53) and several two-component signaling modules (54) as additional negative regulators of M. tuberculosis virulence. In these studies, however, the pleiotropic nature of the mutants may complicate efforts to define the molecular underpinnings of the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Both groups suggested that the operon might encode an importer system involved in recycling of MA. Also, disruption of the mce1operon renders the cells hypervirulent in mice 40,41 . The mutant is unable to induce a strong T-helper 1 (Th1) type T cell immune response and organized granuloma formation in lungs 41 .…”
Section: Mycolic Acidsmentioning
confidence: 99%
“…Thus interaction with epithelia is thought to be crucial for dissemination and to dominate the disease outcome. Besides HBHA, M. tuberculosis has another possible adhesin, designated mycobacterial cell entry protein 1 (Mcep1), of which DNA fragmentation confers on Escherichia coli an ability to invade into nonphagocytic HeLa cells (9), although its precise role as an adhesin remains unclear (10). It is likely that myco-bacteria utilize multiple adhesins to promote attachment to nonprofessional phagocytes.…”
mentioning
confidence: 99%